Exploring Movement in Creative Dance: Introducing 'Dancemblage' in Physical Education Teacher Education - Christopher Engdahl; Simon Ceder (Cappelen Damm Akademisk NOASP, 2023)
Materialities play a crucial role in both the educational practice of physical education (PE), and in physical education teacher education (PETE). This article explores how, often unnoticed, materialities, human as well as non-human, play part in movement exploration in creative dance in PETE. The methodological point of departure is a pedagogical unit in creative dance enacted as part of an optional dance course in a Swedish PETE program where  movement exploration was studied. In the unit, students and a teacher collaboratively explored movement and movement assignments, including the use of materialities. In order to understand how materialities 'co-act' in movement exploration during class, this article provides a post-anthropocentric and Deleuzian approach. The concept dancemblage is introduced both as a way to analyse materiality and as something to work with in pedagogical practice. Moreover, the article suggests that by recognising dancemblages in creative dance teaching, teachers can be given a tool to further learn about learners' explorations and to become open to divergent understandings about what it means to participate in creative dance.